2021
DOI: 10.52810/tpris.2021.100019
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial Fitting Algorithm Based on Neural Network

Abstract: As a method of function approximation, polynomial fitting has always been the main research hotspot in mathematical modeling. In many disciplines such as computer, physics, biology, neural networks have been widely used, and most of the applications have been transformed into fitting problems using neural networks. One of the main reasons that neural networks can be widely used is that it has a certain sense of universal approximation. In order to fit the polynomial, this paper constructs a three-layer feedfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…We can judge the detection of some specific events through target detection and tracking analysis. In this paper, the neural network (NN) technology [ 8 , 9 ] with associative memory (AM) function is studied. And, a sports video athlete detection model has been put forward based on associative memory neural network (AMNN).…”
Section: Introductionmentioning
confidence: 99%
“…We can judge the detection of some specific events through target detection and tracking analysis. In this paper, the neural network (NN) technology [ 8 , 9 ] with associative memory (AM) function is studied. And, a sports video athlete detection model has been put forward based on associative memory neural network (AMNN).…”
Section: Introductionmentioning
confidence: 99%
“…Data mining is a very dynamic research direction in the field of artificial intelligence [ 27 , 28 ] and database, including classification, clustering, regression, association rule discovery, and other mining tasks. Data mining is a process of automatically searching for hidden and special relational information from a large amount of data.…”
Section: Methodsmentioning
confidence: 99%
“…Hu et al classified users into three categories, namely, exceptionally similar, average similar, and very dissimilar, based on the traditional similarity calculation method between users [ 18 ]. Tong et al proposed an improved similarity calculation method for the average similar users [ 19 ]. The experimental results showed that the process could further reduce the error and improve the hit rate of recommendation.…”
Section: Related Workmentioning
confidence: 99%